Additional-levels-based control method for modular multilevel converters with reduced DC-link current ripple - Yu, Qiang (2023)
The high and low order dc-link current ripple can be caused under balanced and unbalanced ac grid/load conditions for three-phase modular multilevel converters (MMCs). To enhance the dc-link current quality, this paper proposes an additional-levels-based control (ALC) method, where the conventional modulation is employed to generate ac-side voltage levels and a model predictive control (MPC) algorithm with reduced calculation burden is developed to produce additional levels for dc-link current performance improvement. Through evaluating the cost function of MPC, the proposed method can reduce both high and low order dc-link current ripple for the MMC. Meanwhile, it avoids disturbing the quality of the ac-side voltage. Besides, the calculation burden of the proposed method is independent of the submodules’ number per arm. The validity and effectiveness of the proposed method have been verified by simulation and experimental results.